2016
DOI: 10.34194/geusb.v37.4356
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigraphic correlation of the western and eastern margins of the Labrador–Baffin Seaway and implications for the regional geology

Abstract: New analyses of the palynological assemblages in 13 offshore wells on the Canadian margin and six on the West Greenland Margin, in conjunction with onshore data, have led to a new biostratigraphic framework for the Cretaceous–Cenozoic strata of the Labrador Sea – Davis Strait – Baffin Bay (Labrador–Baffin Seaway) region and the first broad biostratigraphic correlation of the Canadian and Greenland margins. This framework is based on 167 last occurrences and 18 local/regional peak/common-occurrence events for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 154 publications
(347 reference statements)
1
16
0
Order By: Relevance
“…However, an FO in the middle Turonian Stage and a first common occurrence in the uppermost Turonian Stage was reported by Pearce et al (2003). The FO of R. fucatum in the middle Turonian Stage is described by Costa & Davey (1992) and was also recorded from the North Sea area, Norwegian Sea and West Greenland by Radmacher et al (2015), Pedersen & Nøhr-Hansen (2014) and Nøhr-Hansen et al (2016), respectively; an upper Coniacian FO was reported by Nøhr-Hansen (2012) from the Sorgenfri Formation at Kangerlussuaq, southern East Greenland.…”
Section: Aa Subzone: Senoniasphaera Rotundata (2) Newmentioning
confidence: 82%
“…However, an FO in the middle Turonian Stage and a first common occurrence in the uppermost Turonian Stage was reported by Pearce et al (2003). The FO of R. fucatum in the middle Turonian Stage is described by Costa & Davey (1992) and was also recorded from the North Sea area, Norwegian Sea and West Greenland by Radmacher et al (2015), Pedersen & Nøhr-Hansen (2014) and Nøhr-Hansen et al (2016), respectively; an upper Coniacian FO was reported by Nøhr-Hansen (2012) from the Sorgenfri Formation at Kangerlussuaq, southern East Greenland.…”
Section: Aa Subzone: Senoniasphaera Rotundata (2) Newmentioning
confidence: 82%
“…1) bottomed in a local phonolitic volcano of Turonian age (c. 93 Ma, Knudsen et al 2019), and four wells -Hellefisk-1, Nukik-2, Gjoa G-37 and Hekja O-71 ( Fig. 1)drilled into thick successions of igneous rocks interlayered with and overlain by Paleocene sediments (Hald & Larsen, 1987;Nøhr-Hansen, 2003;Nøhr-Hansen et al 2016). North of 70°N the wells Alpha-1/S1 and Delta-1 bottomed in volcanic rocks overlain by Eocene sediments; the Delta-1 volcanic rocks are dated as of early Eocene age (Nelson et al 2015) and the Alpha-1/S1 rocks are presumed to be latest Paleocene in age (LM Larsen, unpub.…”
Section: A Volcanic Rocksmentioning
confidence: 99%
“…A few metres of sediments overlying the massive volcanic succession at 2548-2553 m are assigned to the ?Danian-Selandian stage, dinocyst palynozones P2/P3a? (Nøhr-Hansen et al 2016). These sediments are overlain by c. 150 m sediments of Selandian age, dinocyst palynozone P4, which gives an age interval of 60.7-59.2 Ma for the two interbedded hyaloclastite intervals.…”
Section: B Nukik-2 Wellmentioning
confidence: 99%
“…Some of these wells reached Precambrian basement (Wasteneys et al, 1996). The oldest sediments are Early Cretaceous syn-rift sediments of the Bjarni Formation, found in only one well close to the basin's western margin, while the remainder of the wells sample Late Cretaceous and younger sediments (Nøhr-Hansen et al, 2016). However, more distal parts of the Saglek Basin have not been well-defined in terms of crustal or sedimentary characteristics (Balkwill & McMillan, 1990;Hinz et al, 1979;van der Linden, 1975).…”
Section: 1029/2017tc004924mentioning
confidence: 99%